Sub-Federal Deliberative Exclusions and Free Trade: Mexico’s Centralized Federalism and Weak Institutional Capacities - López-Vallejo, Marcela; Schiavon, Jorge (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2022)
This article explores the relationship between trade and sub-federal deliberative exclusions in the case of Mexico. Mexican centralized federalism explains the absence of sub-federal governments (SFGs) in the negotiations of free trade agreements, even if they are responsible for dealing with trade outcomes at the local level. This article argues that sub-federal deliberative exclusions are not only evident under the federal allocation of powers but also by their limited institutional capacities (restrictions in budgets and personnel, lack of professionalization, and absence of inter-institutional coordination). This is the case of NAFTA, the USMCA, and the Mexico-European Union Free Agreement in its original and recently renegotiated versions. Despite constraints by federalism and institutional limitations, SFGs engage in trade and investment promotion through inter-institutional agreements (IIAs) allowed by secondary legislation.